A CORRELATIONAL STUDY OF MATHEMATICAL DISPOSITION AND PROBLEM-SOLVING ABILITY IN TRIGONOMETRY - Siti Ruqoyyah; Sukma Murni (Universitas Teknokrat Indonesia, 2025)
This study aims to describe the relationship between mathematical disposition and students’ mathematical problem-solving ability in the topic of trigonometry. The research is grounded on the importance of integrating higher-order thinking skills and positive attitudes toward mathematics in 21st-century learning. A quantitative method with a correlational approach was employed. The research subjects consisted of 20 tenth-grade students from a Madrasah Aliyah in Cimahi City, selected through purposive sampling. The instruments used were a mathematical disposition questionnaire and contextual essay-based problem-solving tests in trigonometry. Data were analyzed descriptively and inferentially using the chi-square test. The results showed that the average students’ problem-solving ability was in the low category with a percentage of 36.09%, while their mathematical disposition was in the moderate category with a percentage of 62.40%. The chi-square test yielded a significance value of 0.757 (p > 0.05), indicating no significant relationship between mathematical disposition and mathematical problem-solving ability. This finding suggests that a positive attitude toward mathematics does not necessarily align with students' ability to solve trigonometric problems. Other factors such as conceptual understanding and learning experiences also play a crucial role. Therefore, mathematics instruction must be holistically designed to foster both cognitive and affective development, supporting students in becoming critical and reflective thinkers.